Sistem Informasi Akademik Serta Penentuan Kelas Unggulan Dengan Algoritama K-Means di SMP Negeri 3 Ubud - Kusuma, Aniek Suryanti; Aryati, Komang Sri (INFOTEKS (Information Technology, Computer and Sciences), 2019)
SMP Negeri 3 Ubud is educational establishments located at Silungan Lotunduh Ubud. SMP Negeri 3 Ubud has excellent class, to define the student entry into superior class using a manual system that is using Microsoft Excel. This system is inefficient because it requires a lot of time when creating. In addition to the data processing of academic, especially a student's scores are still manually so difficult when creating repot. Based on the problems it created an Academic Information System as well as the determination of class excellent using clustering method with K-Means algorithm. with the academic information system and determination superior class computerized then administrative staff easier and faster in processing student data, teacher data and employee data. The method used to determine which class superior that is Clustering K-Means algorithm. With the K-Means algorithm will process the value system and grouping students according to the value closest to the cluster center point. With this system superior class determination more quickly and efficiently